EL juego didáctico para el aprendizaje de la ortografía en los escolares con necesidades educativas especiales de la escuela de educación general básica “IV Centenario”, para el período 2018 - Medina Díaz, Bladimir Alexander (2019)
The present thesis entitled: THE DIDACTIC GAME FOR THE LEARNING OF THE SPELLING IN THE SCHOOLS WITH SPECIAL EDUCATIONAL NEEDS OF THE SCHOOL OF BASIC GENERAL EDUCATION "IV CENTENARY", FOR THE PERIOD 2018, the problem was raised the difficulties that the students present in the learning the spelling, which is given by making it difficult to write, remember and understand the orthographic rules. Whose general objective was: To design didactic games to develop spelling skills in the students with Special Educational Needs of the Basic General Education school "IV Centenario" in the 2018 academic period, which was fulfilled by designing an alternative proposal playing by learning rules spellings; the research was of a scientific-descriptive nature, with a quantitative-qualitative approach and participatory action, using various methods such as: the scientific, inductive, descriptive, techniques such as: the observation guide, interview and instruments such as: the test pedagogical, to students with Special Educational Needs with difficulties in the spelling rules, with didactic games that allowed to develop skills in the learning of the spelling through playful activities, based on storytelling with colorful illustrations and dynamics that led to the improvement of the visual-audio and nogs-motor analyzers, didactic materials that were made so that these students have knowledge tools to deal with spelling problems and improve their learning